İşyerinde Yalnızlığın Örgütsel Sinizm Üzerindeki Etkisinde Tükenmişliğin Aracı Rolünün İncelenmesi - Özdemir, Burak (Muş Alparslan Üniversitesi, 2021)
This research aims to examine the mediating role of burnout in the effect of workplace loneliness on organizational cynicism within the scope of conservation of resources theory. Following this aim, the research population is determined as teachers and data are obtained from 362 teachers between 21.05.2019 and 05.08.2019 using the convenience sampling method. In the research, demographic information form, workplace loneliness scale, burnout scale, and organizational cynicism scale are applied to the participants. The workplace loneliness scale contains two dimensions; social companionship and emotional deprivation. There are three dimensions in the organizational cynicism scale; affective, cognitive, and behavioral cynicism. The burnout scale consists of two dimensions. These are emotional exhaustion with depersonalization and reduced personal accomplishment. Relationships between variables are examined through the structural equation model. Research findings reveal that emotional deprivation positively affects affective, cognitive and behavioral cynicism. In addition, social companionship has negative effects on affective, cognitive and behavioral cynicism. Finally, while emotional exhaustion with depersonalization has a partial mediator role in the relationship between emotional deprivation and affective cynicism and cognitive cynicism, it has a full mediator role in the relationship between emotional deprivation and behavioral cynicism.

Bu araştırma kaynakların korunması teorisi kapsamında işyerinde yalnızlık algısının örgütsel sinizm üzerindeki etkisinde tükenmişliğin aracı rolünü incelemeyi amaçlamaktadır. Bu amaca uygun olarak araştırma evreni öğretmenler olarak belirlenmiş ve kolayda örneklem yöntemi ile 362 öğretmenden 21.05.2019-05.08.2019 tarihleri arasında veriler elde edilmiştir. Araştırmada katılımcılara demografik bilgi formu, işyerinde yalnızlık ölçeği, tükenmişlik ölçeği ve örgütsel sinizm ölçeği uygulanmıştır. İşyerinde yalnızlık ölçeği, sosyal yalnızlık ve duygusal yalnızlık olmak üzere iki boyutu içermektedir. Örgütsel sinizm ölçeğinde üç boyut bulunmaktadır. Bunlar duygusal, bilişsel ve davranışsal sinizmdir. Tükenmişlik ölçeği iki boyuttan oluşmaktadır. Bunlar duygusal tükenme ile duyarsızlaşma ve düşük başarı hissidir. Araştırmada yer alan değişkenler arasındaki ilişkiler yapısal eşitlik modeli ile incelenmiştir. Araştırma bulguları duygusal yalnızlığın, duygusal, bilişsel ve davranışsal sinizmi pozitif yönde etkilediğini göstermektedir. Ayrıca, sosyal yalnızlık duygusal, bilişsel ve davranışsal sinizm üzerinde negatif etkiye sahiptir. Son olarak, duygusal tükenme ile duyarsızlaşma, duygusal yalnızlık ile duygusal sinizm ve bilişsel sinizm arasındaki ilişkide kısmi aracı role sahipken, duygusal yalnızlık ile davranışsal sinizm arasındaki ilişkide tam aracı role sahiptir.
Examining the Mediating Role of the Burnout in the Effect of Workplace Loneliness on Organizational Cynicism
anemon
Keywords: Conservation of Resources Theory; Workplace Loneliness; Burnout; Organizational Cynicism; Kaynakların Korunması Teorisi; İşyerinde Yalnızlık; Tükenmişlik; Örgütsel Sinizm